Pengaruh Metode Kooperatif Number Head Together (NHT) dan Mind Mapping terhadap Hasil Belajar Siswa Mata Pelajaran PAI di SMA Taruna Andigha Kota Bogor. - Elok Mufidah (Jurnal Dirosah Islamiyah, 2023)
Learning outcomes in the subjects of Islamic Religious Education and manners in the material of Hajj, Zakat and waqf of 10th grade students of SMA Taruna Andigha Bogor City are still low. Judging from the data on the learning outcomes of 10th graders in the 2021/2022 academic year, it was found that 36 students (45%) of 80 students achieved the KKM score, namely 75 and 44 students (55%) of 80 students. which is not complete on the material of pilgrimage, zakat and waqf. . This happens because in the delivery of subject matter the teacher emphasizes knowledge to be memorized. The learning method used by the teacher is dominated by the lecture method. More students sit still, and are given assignments only when learning takes place. As a result, students tend to be bored with learning. This problem must be resolved immediately. Steps that can be taken to solve the problem are by changing the learning method used which focuses more on student activity. To overcome these problems, a research entitled "The effect of the number head together and mind mapping method on student learning outcomes in PAI subjects at SMA Taruna Andigha Bogor City was conducted". The subjects of this study were the 10th grade students of SMA Taruna Andigha Bogor City for the academic year 2021/2022, totaling 80 students. This study used a quasi-experimental study carried out in four stages, namely planning, action, observation, and reflection. The method of data collection was done through tests before and after treatment on hajj, zakat and waqf materials. Through observation of student learning activities. The indicator of the success of this research is the average score of student learning outcomes is at least 75, with a minimum mastery percentage of 75%, the percentage of student activity in learning activities is at least 75%. The results showed that the value of Asymp. Sig. (2-tailed) of 0.691 or A.Sig (2-tailed) > 0.05 which means that the learning method using NHT and mind mapping has a good influence on student learning outcomes in PAI subjects in grade 10 SMA Taruna Andigha Bogor City . These results indicate an increase in the value of student learning outcomes after using the number head together and mind mapping methods. The use of cooperative learning methods of the NHT type and mind mapping can improve student learning outcomes in 10th grade PAI subjects at Taruna Andigha High School Bogor City Keywords: Cooperative Learning Model Number head together, mind mapping and learning outcomes.